Nanosized and Enhancement of Solubility Fisetin - Dzakwan, Muhammad; Ganet, Eko Pramukantoro; Rachmat, Mauludin; Wikarsa, Saleh (Asian Journal of Pharmaceutical Research and Development, 2019)
Fisetin (3,3,4,7-tetrahydroxyflavone) is a natural antioxidant that has shown to posses anticancer, antioxidant and anti-inflammatory properties. However, the poor solubility leads to poor bioavailability and limits its development.The aim of the research is to investigate the effect of fisetin nanosuspension using a nanoprecipitation technique and additional stabilizers polysorbat 80, SLS, PVA and Eudragit on particle size average, polydispersity index and zeta potential.The suspensions of microcrystalline FIS were prepared by a nanoprecipitation technique with different proportion of stabilizers fixed. The nanosuspension produced was then characterized using Photon Correlation Spectroscopy (PCS) in term of particle size distribution, polydispersity index, zeta potential and morphology nanosuspensiom (TEM). Result showed fisetin nanosuspension were successfully prepared by anti-solvent precipitation with additional stabilizer SLS and polysorbat 80. The nanosuspension containing polysorbat 80 showed smaller average particle size of 225.7 nm ± 1.31, a polydispersity index of 0.272 ±0.02 and zeta potential -39.3 ± 0.26 was obtained. Conclusion, FIS nanosuspension successfully prepared by nanoprecipitation tecnique with the polysorbate 80 as stabilizer and ethanol as solvent were spherical in shape..